Sosialisasi Penggunaan Pembersih Tangan (Handsanitizer) yang Efektif dalam Upaya Memenuhi Standar WHO dan Protokol Kesehatan Sesuai dengan UU No. 6 Tahun 2018 tentang Karantina Kesehatan di Muhammadiyah Kramat Jati, Jakarta Timur - Marjan Miharja; Erwin Syahruddin; Bionda Johan Anggara; Johan Johan; Gugus Atmoko; Abdillah Umar Lubis; M. Khoerul Anam; Gerry Lesmana (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
WHO determined COVID-19 as a pandemic on March 9, 2020, which is the strongest push for this community service program to be carried out. WHO has published guidance on adjusting the MFIs while managing the risk of a spike in case numbers. WHO publishes guidance on adapting to LKMS, while still managing the risk of a re-increase in the number of cases. A series of measures was developed to help provide guidance to countries in adapting public health measures to various contexts and this provides consideration for decision makers. In connection with the policy of controlling infectious disease outbreaks, Indonesia has Law Number 4 of 1984 concerning Communicable Disease Outbreaks, Government Regulation Number 40 of 1991 concerning Management of Contagious Disease Outbreaks, and Regulation of the Minister of Health Number 1501 / Menkes / Per / X / 2010 concerning Certain Types of Infectious Diseases That Can Cause Outbreaks and Countermeasures. Including various policies to deal with the Covid-19 pandemic issued by the government. One of them is the Large-Scale Social Restrictions or PSBB at the end of March. Citing Article 1 paragraph 11 of Law (UU) Number 6 of 2018 concerning Health Quarantine, PSBB is a limitation of certain activities of residents in an area suspected of being infected with a disease and / or contamination in such a way as to prevent the possibility of spreading disease or contamination. The policy covers at least school and work vacations, restrictions on religious activities and restrictions on activities in public places or facilities, including the socialization of washing hands using hand sanitizer which can be done in certain situations where soap and clean water are not available. For the results to be effective, the hand sanitizer used should contain at least 60% alcohol. This step is a necessity in order to prevent Covid-19 from becoming more widespread. The goal to be achieved from the socialization of good and correct hand washing is to understand the procedures, and be able to practice how to wash hands properly and correctly. It is hoped that in this socialization there will be a change in behavior in the community in washing hands as often as possible properly and correctly.